Estimation of expected cargo oil outflow from tanker involved in casualty - Smailys, Vytautas; Česnauskis, Mindaugas (Transport, 2006)
Modified version of simplified probabilistic methodology, designed for estimation of expected cargo oil outflow from tanker involved in casualty, is proposed. Suggested modified methodology can be used in the circumstances, when only very limited initial input data about the incident and tanker design is available. When applied in certain sea region (for example in Lithuanian sector of the Baltic Sea area), proposed methodology can be used in extremely short time spans, – estimation procedure requires several times less time than standard IMO methodologies, and gives quite insignificant errors of estimated oil outflow.First Published Online: 27 Oct 2010